Lip prints in sex and race determination - Neo, Xiao Xu; Khairul Osman,; Sri Pawita Albakri Amir Hamzah,; Noor Hazfalinda Hamzah, (penerbit ukm, 2012)
Individual identification is an important and challenging task in forensic investigation. Lip print on drinking glass or cigarette butt found at crime scenes may link to a suspect. The aim of this study was to determine the differences in lip print between sexes or races, differences in lip measurement between sexes or races and determine a way to estimate sex and race by using lip print or lip measurements for main races in Malaysia. A total of 134 subjects (67 males and 67 females) of Malay, Chinese and India were recruited from Universiti Kebangsaan Malaysia Campus Kuala Lumpur (UKMKKL), Malaysia. Lip prints were taken by using a lipstick and a transparent cellophane tape. Lip measurements were taken by using electronic digital callipers. Lip prints were classified according to Tsuchihashi classification. Statistical analysis indicated that there was a significant difference in lip print between sexes (p < 0.001) but not in races (p > 0.05). Width of oral opening and the height of lower lip both indicated significant differences between sexes (p < 0.001) while the height of upper lip and lower lip each indicated significant differences between races (p < 0.05). However, there was no significant interaction between sexes and races for all lip measurements. Formulae for sex and race determination were calculated with Classification Tree when there was significant difference between every comparison. Tables of accuracy percentage and performance evaluation for method in categorizing sex or race by using lip print or lip measurement were made. For validation of method in sex determination based on the formulae formed, accuracy in females is 90% and 65% in males. Therefore, overall percentage of accuracy in sex determination was 77.5%. This study can provide a preliminary idea about the use of lip prints in sex or race determination among Malaysian population.